Magnetic resonance used as a differential diagnostic tool between inflammatory cancer of the sigmoid and acute sigmoid diverticulitis - Cornel Dragos Cheregi; Teodora Gabriela Alexescu; Andrei Vasile Pascalau; Ovidiu Laurean Pop; Calin Magheru; Ioana Maria Muresan; Nicoleta Ramona Suciu; Maur Sebastian Horgos; Mihai Stefan Muresan (Journal of Mind and Medical Sciences)
Sigmoid diverticulitis is a common disease characterized by a well-standardized diagnostic approach and treatment. Colorectal cancer is the third most common malignancy worldwide, irrespective of gender. In 2020, CRC global-related mortality rate was estimated at 935 173 cases, with an incidence of 9.3% in men and 9.5% in women. The diagnosis of acute diverticulitis is always made by performing a contrast-enhanced-computed tomography (CT) of the abdomen. Current diagnosis guidelines do not recommend the use of a magnetic resonance imaging (MRI) for further and more precise assessment of a suspected sigmoid diverticulitis diagnosed by CT. Early lower-gastrointestinal (lower-GI) endoscopy is rarely conducted; thus, the diagnosis delay could have a negative impact over the oncological outcome of the disease. Few and scarce data can be found related to this issue, with only a recent Swedish study paying attention towards early identification of neoplastic disease residing on a background of sigmoid diverticulitis, facilitated by MRI. The purpose of this study is to evaluate the feasibility of systematically performing an abdominal MRI included in the primary assessment of acute diverticulitis already diagnosed by CT, in order to argument in favor of an early lower-GI endoscopy where a positive MRI for neoplasia is found.